2023
DOI: 10.1051/0004-6361/202244894
|View full text |Cite
|
Sign up to set email alerts
|

55 Cancri e’s occultation captured with CHEOPS

Abstract: Past occultation and phase-curve observations of the ultra-short period super-Earth 55 Cnc e obtained at visible and infrared wavelengths have been challenging to reconcile with a planetary reflection and emission model. In this study, we analyse a set of 41 occultations obtained over a two-year timespan with the CHEOPS satellite. We report the detection of 55 Cnc e's occultation with an average depth of 12 ± 3 ppm. We derive a corresponding 2-σ upper limit on the geometric albedo of A g < 0.55 once decontamin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
1
4
1
Order By: Relevance
“…I now suggest an alternative interpretation of the observations reported by Demory et al (2016aDemory et al ( , 2016b, Tamburo et al (2018), Demory et al (2023), and Meier Valdés et al (2023). When the optical/visible secondary eclipse depths are consistent with being zero, this is interpreted as the observations probing mainly the bare rocky surface of the dayside of 55 Cancri e. To be consistent with zero optical/visible eclipse depth, the geometric albedo of the surface must be close to zero.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…I now suggest an alternative interpretation of the observations reported by Demory et al (2016aDemory et al ( , 2016b, Tamburo et al (2018), Demory et al (2023), and Meier Valdés et al (2023). When the optical/visible secondary eclipse depths are consistent with being zero, this is interpreted as the observations probing mainly the bare rocky surface of the dayside of 55 Cancri e. To be consistent with zero optical/visible eclipse depth, the geometric albedo of the surface must be close to zero.…”
Section: Discussionsupporting
confidence: 59%
“…These recently reported observations by the CHEOPS space telescope (Meier Valdés et al 2022Demory et al 2023), as well as upcoming eclipse observations by the James Webb Space Telescope (JWST), 4 motivate a qualitatively different approach of interpreting the data of 55 Cancri e. In the current study, it is suggested that the reported observations collectively describe a thin, transient, outgassed atmosphere that does not survive over long timescales, because atmospheric escape dominates the outgassing flux.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Repeating this exercise in the CHEOPS band yields occultation depths of 5 ppm and 10 ppm for our BSE and Venusian models, respectively. While these models at first glance are discrepant from existing single Spitzer (Mercier et al 2022) and CHEOPS (Demory et al 2023) observed occultation depths of 209 47 50 -+ ppm and 12 ± 3 ppm, respectively, the models fall within the full range of observed variable occultations (Demory et al , 2023. In light of the lack of consensus on the observed variability's origin, it is not immediately clear whether our models are constrained by existing photometric data.…”
Section: Data and Modelscontrasting
confidence: 72%